Advertising - Eason, J. C. M. (Statistical and Social Inquiry Society of Ireland, 1943)
In submitting this paper on the subject of Advertising I would make it clear that although I have certain contacts which provide me with some knowledge as regards the use of advertising, there are many specialised activities of the practitioner in advertising of which I have no practical experience, and on the economic side I depend upon higher authority than my own experience. It is not in any sense a technical paper on Advertising, but it purports to summarise certain aspects of this business activity, and to furnish some comments upon criticisms, which have been rather frequent recently, of its utility. Whatever may be the reason advertising is attracting more attention than formerly; people who do not like it are becoming more prominent, and their dislikes are being advertised. When the Economic Journal includes a special article on the subject; when the B.B.C. allows Mr. Max Beerbohm to ventilate his views which, while couched in humorous vein, undoubtedly disturbed the minds of a number of persons interested in advertising (both the users and the sellers of space); and when Mr. Samuel Courtauld in his article on the "Relations of Government and Industry" devotes quite a number of paragraphs to depreciating its value, I think there is no great excuse needed for bringing the subject under the notice of this learned Society.
Read on 20th November, 1942
Keywords: Advertising; Media; 314.15